PENGARUH EKSPOR DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 1980-2006 - Sutawijaya, Adrian (LPPM Universitas Terbuka, 2010)
Economic growth basically measures the ability of a country to expand output faster rate than population growth rate. Exports and investment are important in increasing the rate of economic growth. Exports would generate foreign exchange that will be used to finance imports, especially imports of raw materials and capital goods needed in the production process which will shape the value added. Aggregation of the value added generated by all units of production in the economy is the value of Gross Domestic Product. Investment or capital investment is also a component of value added to national building, which is the purchase of capital goods and production equipment to improve the ability to produce goods needed in the economy. Using OLS method, it shows that economic growth is positively correlated to government investment, private investment, and non oil exports. While,oil and gas export gives negative influence to economic growth. Overall government investment, private investment, oil and gas exports and non-oil exports are able to explain variation economic growth of 98.9 percent while the rest explained by other factors.